1986
DOI: 10.1182/blood.v68.5.1142.bloodjournal6851142
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of large granular lymphocyte proliferations: delineation of two major subtypes

et al.

Abstract: Two major types of lymphocytosis of large granular lymphocytes (LGLs) were observed. The proliferating LGLs in each type had distinct immunophenotypes, functional characteristics, and probably belonged to different cell lineages. The more common form (Type A) consisted of cells derived from the T cell lineage and had the T suppressor/cytotoxic phenotype (T11+, T3+, T8+). The expression of the Leu 7 and HLA-DR antigen was variable. These cells did not have natural killer (NK) function but showed a variable degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Another major difference between our patients with CNKL and those with T-LGL leukaemia was that 26% of patients with T-LGL leukaemia but only 6% with CNKL had rheumatoid arthritis. The close association between T-LGL leukaemia and rheumatoid arthritis is well established (Loughran & Starkebaum, 1987), but not between rheumatoid arthritis and CNKL (Chan et al, 1986(Chan et al, , 1992Oshimi et al, 1993). In addition to rheumatoid arthritis, patients with T-LGL leukaemia often have laboratory and clinical evidence of autoimmune phenomena (Dhodapkar et al, 1994b;Gentile et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Another major difference between our patients with CNKL and those with T-LGL leukaemia was that 26% of patients with T-LGL leukaemia but only 6% with CNKL had rheumatoid arthritis. The close association between T-LGL leukaemia and rheumatoid arthritis is well established (Loughran & Starkebaum, 1987), but not between rheumatoid arthritis and CNKL (Chan et al, 1986(Chan et al, , 1992Oshimi et al, 1993). In addition to rheumatoid arthritis, patients with T-LGL leukaemia often have laboratory and clinical evidence of autoimmune phenomena (Dhodapkar et al, 1994b;Gentile et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These cells have phenotypic and functional characteristics identical to those of peripheral blood NK cells. Chan et al (437) observed that nine patients with CD3+…”
Section: In Uivo Nk Cells Suppress Hematopoietic Progenitors In Mice mentioning
confidence: 99%
“…'6, 24-'5 Two distinct groups of LDGL patients may be recognized on the basis of the expression of CD3 antigen and T-cell receptor. 26 The larger group is characterized by cases in which proliferating cells express CD3 determinants and display low NK activity. In the second group of patients, GL are CD3-and display higher NK activity in vitro.…”
Section: Discussionmentioning
confidence: 99%